Case Study on Sustainability of Rural Sanitation Marketing in Vietnam - Sijbesma, Christine; Truong, Truong Xuan; Devine, Jacqueline (World Bank, Washington, DC, 2014)
From 2003 to 2006, a rural pilot project was conducted in Vietnam with technical support from the non-governmental organization (NGO) International Development Enterprises (IDE) and funding from Danish International Development Assistance (DANIDA). The project tested whether a sanitation marketing approach could improve rural access to sanitary toilets in 30 communes in six districts of the coastal provinces of Thanh Hoa and Quang Nam. Research for the case study took place between June and August 2009. Local sanitation statistics were collected in all study communes. Semi-structured interviews were held with the promoters, providers, and some local government authorities. Interviews were held with district and provincial authorities and at a national level with the Non Governmental Organizations (NGOs), national authorities, and donors involved in rural sanitation. With the help of participatory tools, focus group discussions were held with sixty-one householders who had built sanitary toilets or upgraded their unsanitary ones, and sixty householders who had either no toilet or a still unsanitary one. Finally, the study team visited a very small and non-random sample of installed toilets to observe the quality of construction and hygiene as per the national standards of the Ministry of Health.